13x-68=-7x+12

Simple and best practice solution for 13x-68=-7x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-68=-7x+12 equation:


Simplifying
13x + -68 = -7x + 12

Reorder the terms:
-68 + 13x = -7x + 12

Reorder the terms:
-68 + 13x = 12 + -7x

Solving
-68 + 13x = 12 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-68 + 13x + 7x = 12 + -7x + 7x

Combine like terms: 13x + 7x = 20x
-68 + 20x = 12 + -7x + 7x

Combine like terms: -7x + 7x = 0
-68 + 20x = 12 + 0
-68 + 20x = 12

Add '68' to each side of the equation.
-68 + 68 + 20x = 12 + 68

Combine like terms: -68 + 68 = 0
0 + 20x = 12 + 68
20x = 12 + 68

Combine like terms: 12 + 68 = 80
20x = 80

Divide each side by '20'.
x = 4

Simplifying
x = 4

See similar equations:

| (1/3*9)3 | | 3x+26/5=7 | | n+3n=180 | | 0.8(m+4)-0.3m= | | 5x=-6x-22 | | -6-j=4+j | | -27=-2x-7 | | -p-4=-12 | | -9-6x=-21 | | 8(2n-1)=6(6n+3)+8 | | 3/-4 | | 5p-16=10 | | -7x-12=2x-(5x-8) | | (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) | | 7/1(4/1) | | -1(2+5)=-14 | | 53y=2 | | 4n^2-2=14 | | -3n=7n+10 |

Equations solver categories